Work stress of teachers of 1º and 2º cycles of Basic School Education in Paraguay - Ayala-Ortiz, Lourdes Irma (2023)
The objective of the research is to analyze the work stress of teachers of the 1st and 2nd cycles of Basic School Education (EEB) in Paraguay. The methodology used was descriptive, quantitative, cross-sectional, applying a questionnaire to 75 teachers from official educational institutions in the city of Encarnación. The results show that teachers present an average level of work stress, taking into account the dimensions, the average level is presented in emotional exhaustion and personal fulfillment for teachers of both sexes, but not in depersonalization. The presence of work stress occurs at different levels in relation to demographic variables such as age, years of experience in teaching, shift in which he teaches, and the location of the institution, be it urban or rural, where he teaches. The study is concluded by highlighting the need to have comprehensive programs that provide permanent support to teachers and generate control alternatives over their work and labor demands; in order to prevent adverse effects on the health of the professional.